The Third International Workshop on Dynamic Scheduling Problems: Extended Abstracts - Stanisław Gawiejnowicz (ed.) (Polish Mathematical Society, 2021)
This book contains extended abstracts of a plenary lecture and papers presented at the Third International Workshop on Dynamic Scheduling Problems, July 5th–6th, 2021, Poznań, Poland.
Keywords: adjacent job sequence; adjacent scenario; agent scheduling; assembly line; bi-criteria optimization; choice of opponent; complexity; conditional DAG; data gathering networks; deteriorating jobs; discrete scenario; dynamic programming; FFD; fl ow shop; forgetting e ects; FPTAS; heuristics; job rejection; LAPT rule; learning eff ects; line side placement; local search; LPT rule; makespan; mixed-criticality scheduling; moving conveyor; multiple round sports tournament; open shop; parallel machines; parallel processing; performance criteria; periodic availability; position-dependent jobs; professional tennis data; reinforcement learning; relative robust optimization; resource allocation; resource-dependent processing times; scheduling; single machine; step-learning; time-dependent scheduling; total completion time; V-shape property; variable communication speed; varying-speed processors; walking time; worst-case ratio